Internally mixed anti-seepage and anti-rust concrete
By using stearic acid dispersion, zinc oxide or structured zinc oxide as anti-seepage rust resistors in concrete, the problems of insufficient durability and environmental protection of reinforced concrete in the prior art are solved, and the anti-seepage rust resistance performance is significantly improved. effect.
Patent Information
- Application Number
- CN202311032060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The prior art has environmental protection problems in improving the durability of reinforced concrete, and it is difficult to effectively prevent the penetration of chloride ions and other corrosive substances, resulting in corrosion of steel bars.
Stearic acid dispersion, zinc oxide or structured zinc oxide are used as anti-seepage rust-resisting agents to enhance its anti-seepage rust resistance by improving the hydrophobic properties of concrete and gel formation ability.
It significantly improves the anti-seepage rust resistance of concrete, reduces the penetration of chloride ions and other corrosive substances, extends the service life of steel bars, and is environmentally friendly and avoids the use of harmful substances such as phosphorus.
Smart Images

Figure CN117049844B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to an internally mixed anti-seepage and anti-rust concrete. Background Art
[0002] The durability of reinforced concrete is a problem faced by the whole world. Steel corrosion, chemical erosion, concrete carbonization, freeze-thaw damage, alkali-aggregate reaction, etc. can all cause insufficient structural durability. Among them, the main reason for accelerating concrete damage is steel corrosion. The main factor leading to steel corrosion is Cl - Intrusion and carbonization of concrete materials. In general atmospheric environment, steel bar corrosion in concrete is mainly caused by concrete carbonization. In construction projects in coastal areas, Cl - It is the primary cause of steel corrosion in concrete.
[0003] In actual projects, steel bar rust inhibitors are usually added to improve the durability of reinforced concrete. Studies have shown that the higher the amount of steel bar rust inhibitor added, the lower the early strength of cement mortar; the appropriate amount of steel bar rust inhibitor added can increase the folding compression ratio and later strength of mortar, which is beneficial to improving the concrete's crack resistance and resistance to chloride ion penetration. CN113307536A discloses an anti-corrosion and rust-proof type anti-cracking and waterproofing agent, which comprises 25-35% of anti-corrosion and rust-proof components, 35-55% of expansion components, and 20-30% of waterproof and anti-seepage components by mass percentage; the anti-corrosion and rust-proof components comprise 80-98% of anti-corrosion components and 2-20% of rust-proof components by mass percentage; the anti-corrosion components are any one or more mixtures of ultrafine mineral powder, ultrafine fly ash, and ultrafine silica ash; the rust-proof components comprise any one or more mixtures of sodium hexametaphosphate, triisopropanolamine, sodium carbonate, and anhydrous sodium metasilicate; the waterproof and anti-seepage components comprise 35-70% of sodium bentonite, 8-25% of calcium formate, 10-25% of organic silane water repellent, 2-10% of polycarboxylic acid water reducer, and 8-20% of sodium silicate by mass percentage. The concrete prepared by adding the anti-corrosion and rust-proof type anti-cracking and waterproofing agent to cement mortar has good chloride ion and sulfate resistance. However, the phosphorus contained in its ingredients may have an impact on the environment.
[0004] Therefore, it is necessary to provide an environmentally friendly anti-seepage and rust-proof concrete. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides an internally mixed anti-seepage and anti-rust concrete, which comprises, by mass, 200-300 parts of cement, 400-600 parts of river sand, 800-1200 parts of crushed stone, 50-150 parts of fly ash, 50-150 parts of mineral powder, 5-10 parts of water reducer, 6-24 parts of anti-seepage and anti-rust agent, and 100-200 parts of water;
[0006] The anti-seepage and rust inhibitor comprises at least one of stearic acid dispersion, zinc oxide or structured zinc oxide.
[0007] Concrete is the first barrier to protect steel bars from the invasion of corrosive ions. During the cement hydration process, the pore solution formed inside the concrete is strongly alkaline (pH value is between 12.5 and 13.8, depending on the type of cement used). Under strong alkaline conditions, the steel bars can react with the hydroxide ions in the pore solution to form a passivation film to isolate the corrosive ions, making the steel bars in a passivated state and protecting them from corrosion. However, concrete is a porous material that cannot prevent the invasion of corrosive ions, and the environment in which concrete is located usually has Cl – , CO2, SO2 and other substances, which undergo redox reactions in concrete, reduce the pH value of the pore solution, thereby destroying the passive film of the steel bars and causing corrosion of the steel bars. Stearic acid is the sodium salt of stearic acid. Stearic acid has both hydrophilic and hydrophobic parts, which are carboxylate and long hydrocarbon chains. Adding stearic acid to concrete may improve the hydrophobic properties of concrete, thereby inhibiting the penetration of electrolyte solutions into the concrete.
[0008] Some studies have shown that nanoparticles can enhance gel formation, and higher concentrations of gel fill the internal pores of concrete, thereby inhibiting Cl – The nanoparticles can also act as a barrier to prevent the penetration of Cl into the concrete, thus enhancing its durability. – Penetration into the interior of concrete. Zinc oxide, commonly known as zinc white, has a stable structure, simple preparation method, and easy control of morphology and specific surface area. It is widely used in various fields. Adding zinc oxide to the concrete system may improve the rust resistance of concrete. At the same time, forming a graded structure of zinc oxide may promote the interaction between zinc oxide and gel materials.
[0009] Furthermore, the anti-seepage and rust inhibitor is prepared by mixing a stearic acid dispersion with zinc oxide or structured zinc oxide in a mass ratio of 3:1 to 1:3.
[0010] Furthermore, the preparation method of the structured zinc oxide is, in parts by mass,
[0011] 2-5 parts of soluble zinc salt, 1-3 parts of hexamethylenetetramine, 0.2-0.5 parts of ammonium fluoride and 50-100 parts of water are mixed, followed by hydrothermal reaction, and insoluble matter is collected and calcined to obtain structured zinc oxide.
[0012] Furthermore, the soluble zinc salt is at least one of zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc chloride.
[0013] Furthermore, the hydrothermal reaction is maintained at 150-200° C. for 10-20 hours.
[0014] Furthermore, the calcination is maintained at 300-500° C. for 2-5 hours.
[0015] Furthermore, the stearic acid dispersion is an ethanol solution of stearic acid with a mass fraction of 1 to 3%.
[0016] Further, the cement is ordinary Portland cement;
[0017] The particle size of the river sand is 0.15 to 4.75 mm;
[0018] The particle size of the crushed stone is 5 to 10 mm;
[0019] The fly ash is first-grade fly ash;
[0020] The mineral powder is S95 grade mineral powder;
[0021] The water reducing agent is a polycarboxylate water reducing agent.
[0022] Furthermore, the particle size of the zinc oxide is 50±5 nm.
[0023] The present invention also provides a method for preparing the internally mixed anti-seepage and anti-rust concrete, comprising:
[0024] The anti-seepage and rust inhibitor, mineral powder, water reducing agent and water are mixed to obtain a premix;
[0025] Cement, river sand, crushed stone and fly ash are mixed and then added into premix, and stirred to obtain internally mixed anti-seepage and anti-rust concrete.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention uses stearic acid dispersion, zinc oxide or structured zinc oxide as an anti-seepage and rust inhibitor for concrete. Results show that zinc oxide or structured zinc oxide can enhance the formation of gel, and gel with a higher concentration fills the internal pores of concrete. Stearic acid dispersion can improve the hydrophobicity of concrete. Stearic acid dispersion, zinc oxide or structured zinc oxide are mixed in a certain proportion to form a rust inhibitor, which can significantly improve the anti-seepage and rust inhibition performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The scanning electron microscope image of the structured zinc oxide of Example 8 of the present invention is shown.
[0029] Figure 2 shows a scanning electron microscope image of a concrete specimen prepared in Example 7 of the present invention;
[0030] Figure 3 The scanning electron microscope image of the concrete specimen prepared in Example 8 of the present invention is shown. DETAILED DESCRIPTION
[0031] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0032] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Introduction of some raw materials used in the embodiments of the present invention:
[0034] Ordinary Portland cement PO 42.5, purchased from Harbin Cement Co., Ltd. of Yatai Group;
[0035] Polycarboxylate water reducer, model 002, purchased from Anhui Huashi Nanotechnology Co., Ltd.;
[0036] Zinc oxide, particle size 50 ± 5 nm, spherical, purchased from Hangzhou Jikang New Materials Co., Ltd.;
[0037] The stearic acid ethanol solution used in the embodiment is prepared by dissolving stearic acid in anhydrous ethanol; the particle size of the river sand is 0.15-4.75 mm; the particle size of the crushed stone is 5-10 mm; the fly ash is first-grade fly ash, and the mineral powder is S95 grade mineral powder. These will not be repeated. These raw materials are common raw materials and can be directly purchased from the market.
[0038] Example 1
[0039] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0040] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 12 kg of zinc oxide, and 150 kg of water;
[0041] Step 2: Mix zinc oxide, mineral powder, polycarboxylate water reducer and water at a speed of 50 rpm for 120 seconds to obtain a premix;
[0042] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0043] Example 2
[0044] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0045] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 24 kg of zinc oxide, and 150 kg of water;
[0046] Step 2: Mix zinc oxide, mineral powder, polycarboxylate water reducer and water at a speed of 50 rpm for 120 seconds to obtain a premix;
[0047] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0048] Example 3
[0049] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0050] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 9 kg of 2% stearic acid ethanol solution, and 150 kg of water;
[0051] Step 2: Mixing a 2% by mass stearic acid ethanol solution, mineral powder, polycarboxylate water reducer and water at a speed of 50 rpm for 120 seconds to obtain a premix;
[0052] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0053] Example 4
[0054] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0055] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 12 kg of 2% stearic acid ethanol solution, and 150 kg of water;
[0056] Step 2: Mixing a 2% by mass stearic acid ethanol solution, mineral powder, polycarboxylate water reducer and water at a speed of 50 rpm for 120 seconds to obtain a premix;
[0057] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0058] Example 5
[0059] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0060] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 24 kg of 2% stearic acid ethanol solution, and 150 kg of water;
[0061] Step 2: Mix 2% stearic acid ethanol solution, mineral powder, polycarboxylate water reducer and water at a speed of 50 rpm for 120 seconds to obtain a premix;
[0062] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0063] Example 6
[0064] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0065] Step 1, weigh 300kg of ordinary Portland cement PO 42.5, 500kg of river sand, 1000kg of crushed stone, 50kg of fly ash, 50kg of mineral powder, 10kg of polycarboxylate water reducer, 9kg of 2% stearic acid ethanol solution, 9kg of zinc oxide, and 150kg of water;
[0066] Step 2: 2% stearic acid ethanol solution, zinc oxide, mineral powder, polycarboxylate water reducer and water are mixed to obtain a premix;
[0067] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0068] Example 7
[0069] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0070] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 9 kg of 2% stearic acid ethanol solution, 6 kg of zinc oxide, and 150 kg of water;
[0071] Step 2: 2% stearic acid ethanol solution, zinc oxide, mineral powder, polycarboxylate water reducer and water are mixed to obtain a premix;
[0072] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0073] Example 8
[0074] A method for preparing an internally mixed anti-seepage and anti-rust concrete, comprising the following steps:
[0075] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, 9 kg of 2% stearic acid ethanol solution, 6 kg of structured zinc oxide, and 150 kg of water;
[0076] Step 2: 2% stearic acid ethanol solution, structured zinc oxide, mineral powder, polycarboxylate water reducer and water are mixed to obtain a premix;
[0077] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain internally mixed anti-seepage and anti-rust concrete.
[0078] Among them, the preparation method of structured zinc oxide is to mix 0.05 kg of zinc acetate dihydrate, 0.02 kg of hexamethylenetetramine, 0.003 kg of ammonium fluoride and 1 kg of water at a speed of 300 rpm for 10 minutes, then hydrothermally react at 180°C for 12 hours, filter, wash, and dry, collect the insoluble matter, and calcine at 500°C for 3 hours to obtain structured zinc oxide.
[0079] Comparative Example
[0080] A method for preparing concrete, comprising the following steps:
[0081] Step 1: weigh 300 kg of ordinary Portland cement PO 42.5, 500 kg of river sand, 1000 kg of crushed stone, 50 kg of fly ash, 50 kg of mineral powder, 10 kg of polycarboxylate water reducer, and 150 kg of water;
[0082] Step 2: mixing mineral powder, polycarboxylate water reducer and water to obtain a premix;
[0083] Step 3: Mix ordinary Portland cement PO 42.5, river sand, crushed stone and fly ash, add premix, and stir to obtain concrete.
[0084] Test Case
[0085] Test Example The morphology of the structured zinc oxide in Example 8 of the present invention is as follows Figure 1 As shown, it can be seen that structured hierarchical nanosheet layers of zinc oxide were successfully prepared.
[0086] The water absorption rate of the materials prepared in Examples 1 to 9 and the comparative example was tested with reference to JC / T 474-2008 standard for mortar and concrete waterproofing agents. The results are shown in Table 1.
[0087] Table 1 Water absorption results
[0088] Water absorption (%) Example 1 5.2 Example 2 9.6 Example 3 3.8 Example 4 5.1 Example 5 7.8 Example 6 5.0 Example 7 4.7 Example 8 4.2 Comparative Example 4.6
[0089] Comparing Examples 1 to 2 and the comparative example, a certain mass of zinc oxide will significantly increase the water absorption rate of concrete. This is because zinc oxide has a small particle size and a large specific surface area, and has a strong ability to attract water molecules. Excessive zinc oxide hinders the formation of hydration products in the early stage, delays the hydration of cement, and causes the concrete porosity to be too large, thereby significantly increasing the water absorption rate. Comparing Examples 3 to 5 and the comparative example, the amount of stearic acid added increases, and the water absorption rate gradually increases. This is because a small amount of stearic acid can improve the overall hydrophobicity of concrete, but the increase in stearic acid hinders the hydration reaction of cement, thereby increasing free water. It promotes the formation of additional porosity. As the porosity of concrete increases, water can easily enter the pore structure of concrete, thereby causing the hydrophobicity to increase. Comparing Examples 6 to 7 and the comparative example, it can be seen that compounding stearic acid and zinc oxide can inhibit their effects on cement hydration. In particular, Example 8 with structured zinc oxide has the lowest water absorption, which may be due to the light lamellar structure of structured zinc oxide, which can promote early hydration, and stearic acid can also improve the overall hydrophobicity.
[0090] Referring to GB / T50081-2019 standard for test methods for physical and mechanical properties of concrete, the concrete material was made into 100mm×100mm×100mm specimens, cured at 20±2℃ and relative humidity above 95% for 28 days, and the compressive strength test was carried out. The results are shown in Table 2.
[0091] Table 2 Compressive strength results
[0092] 28-day compressive strength (MPa) Example 2 45.3 Example 5 49.2 Example 7 62.3 Example 8 64.8 Comparative Example 59.3
[0093] The test results in Table 2 are basically consistent with the water absorption test results, because too much zinc oxide and stearic acid lead to increased pores, resulting in a decrease in compressive strength. At the same time, Example 8 has the highest compressive strength.
[0094] The microstructures of the specimens made in Example 7 and Example 8 after curing for 28 days were also tested. Figure 2 and Figure 3 It can be seen that the concrete specimen prepared in Example 8 has a smaller porosity, which is consistent with the compressive strength test results.
[0095] The concrete material was made into a Φ100mm×50mm specimen and cured at 20±2℃ and relative humidity above 95% for 28 days. The chloride ion migration coefficient of the concrete specimen was tested using the rapid chloride ion migration coefficient method (RCM method). The results are shown in Table 3.
[0096] Table 3 Chloride ion migration coefficient results
[0097]
[0098] It can be seen from the test results in Table 3 that the internally mixed anti-seepage and anti-rust concrete prepared in Example 7 and Example 8 has good resistance to chloride ion migration.
[0099] The concrete material was poured into a 70mm×70mm×70mm mold, and a Φ100mm×50mm HRB335 steel bar was inserted into the concrete material, wherein a copper wire was welded in the middle of the HRB335 steel bar. After curing for 7 days at 20±2℃ and relative humidity above 95%, epoxy resin was coated on the upper and lower ends of the specimen, and then immersed in a 3.5% mass fraction sodium chloride solution for 24 hours, the concrete specimen was used as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the counter electrode, the corrosion current of different concrete materials was tested, and the results are shown in Table 4.
[0100] Table 4 Corrosion current results
[0101] <![CDATA[Corrosion current (μA / cm 2 )]]> Example 7 4.231 Example 8 6.359 Comparative Example 1.335
[0102] From the results in Table 4, it can be seen that compared with ordinary concrete, using stearic acid dispersion, zinc oxide or structured zinc oxide as the anti-seepage and rust inhibitor of concrete can significantly reduce the corrosion current. This is because they have smaller pores, lower water absorption, and higher strength, which reduces the diffusion of chloride ions into the interior of the concrete.
[0103] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Internally mixed anti-seepage and anti-rust concrete, characterized in that: In terms of mass, it includes 200-300 parts of cement, 400-600 parts of river sand, 800-1200 parts of crushed stone, 50-150 parts of fly ash, 50-150 parts of mineral powder, 5-10 parts of water reducer, 6-24 parts of anti-seepage and rust inhibitor, and 100-200 parts of water; The anti-seepage and rust inhibitor is prepared by mixing a stearic acid dispersion and structured zinc oxide in a mass ratio of 3:1 to 1:3; the stearic acid dispersion is an ethanol solution of stearic acid with a mass fraction of 1 to 3%; The preparation method of the structured zinc oxide is calculated by weight: 2-5 parts of soluble zinc salt, 1-3 parts of hexamethylenetetramine, 0.2-0.5 parts of ammonium fluoride and 50-100 parts of water are mixed, followed by hydrothermal reaction, and insoluble matter is collected and calcined to obtain structured zinc oxide; The hydrothermal reaction is maintained at 150-200° C. for 10-20 hours; The calcination is maintained at 300-500° C. for 2-5 hours.
2. The internally mixed anti-seepage and anti-rust concrete according to claim 1 is characterized in that: The soluble zinc salt is at least one of zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc chloride.
3. The internally mixed anti-seepage and anti-rust concrete according to claim 1 is characterized in that: The cement is ordinary Portland cement; The particle size of the river sand is 0.15~4.75mm; The particle size of the crushed stone is 5-10 mm; The fly ash is first-grade fly ash; The mineral powder is S95 grade mineral powder; The water reducing agent is a polycarboxylate water reducing agent.
4. A method for preparing the internally mixed anti-seepage and anti-rust concrete according to any one of claims 1 to 3, characterized in that: include, The anti-seepage and rust inhibitor, mineral powder, water reducing agent and water are mixed to obtain a premix; Cement, river sand, crushed stone and fly ash are mixed and then added into premix, and stirred to obtain internally mixed anti-seepage and anti-rust concrete.
Citation Information
Patent Citations
Anti-corrosion and anti-rust type anti-crack waterproof agent
CN113307536A
Rhombus zinc oxide nanorod array and preparation method thereof
CN103288122A
Concrete and high-permeating-resistance impedance agent for same
CN108529980A
Anti-corrosion and anti-rust concrete and preparation method thereof
CN110981301A